Relationship between anthropometric characteristics, handgrip strength and ball-handling performance in young basketball players - Apostolidis, N.; Zacharakis, E.; Kostopoulus, N.; Bolatoglou, T. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
In basketball game the anthropometric characteristics and especially arms` and hands` length can define handgrip strength. Furthermore, the anthropometric characteristics can define the performance of the young basketball players (Visnapuu & Jurimae, 2007). The aim of the present study was to investigate the relation between arms` and forearms` length and hand surface with the handgrip strength, as well as between handgrip strength and the basketball handling as it is expressed by shooting and dribbling skill (A.A.H.P.E.R., 1984). Methods: A sample of 105 young basketball players (aged 13.5 years) volunteered to participate in the following measurements and tests: (a) Anthropometric measurements of body high, length of arms, forearms and fingers, as well as hand surface and (b) handgrip strength, shooting and dribbling skill tests [1]. For the statistical analyses were conducted: (a) Pearson correlation for the initial exploration of the relation between all of the measured variables and (b) six separate stepwise regression analyses in order to confirm the predictability of the anthropometric characteristics against handgrip strength, and of the handgrip strength against dribbling and shooting skills. Statistical significance was accepted at p<0.05 level. Results: Strong correlations were revealed among handgrip strength and all of the measured variables. The results of the regression analyses revealed significant predictability of the anthropometric characteristics against handgrip strength and also of the handgrip strength against dribbling and shooting skills. Discussion: The results of the study are in accordance with the recent literature, namely, the anthropometric characteristics of body high, arms and forearms length, as well as the hand surface are clear predictors of the handgrip strength. Regarding the second part of the study, handgrip strength is also clear predictor of shooting and mostly dribbling abilities. Conclusively, the longer of the arms and hands, the stronger of the handgrip, and the stronger of the handgrip, the better of the basketball handling.